Pulmonary embolism: a diagnostic challenge - Tavares, Nilza Tavares (2023)
Introduction: Venous thromboembolism includes deep vein thrombosis and pulmonary embolism. In Portugal, the incidence of pulmonary embolism was estimated at 35 per 100,000 people. The clinical manifestations of pulmonary embolism are nonspecific. In this case report, the authors want to alert to the challenge of clinical suspicion of pulmonary embolism, especially in primary care. Case description: 76-year-old man, with a personal history of hypertension, dyslipidaemia, obesity, depression, benign prostatic hypertrophy, varicose veins, chronic venous insufficiency, and deep vein thrombosis in 2012. He referred to the beginning of fatigue after a urological surgery. A month after he goes to his health unit, in a period of absence of the family doctor, and to the hospital emergency service. He was also evaluated in the postoperative urology consultation, where he reported the persistence of fatigue. During the family physician appointment, he described his fatigue as a feeling of dyspnea and chest discomfort. He was in good general condition, with no respiratory distress syndrome. Blood pressure 134/82mmHg, heart rate 85bpm, peripheral oxygen saturation 92%. Cardiac and pulmonary sounds were normal. Absence of signs of deep or superficial venous thrombosis. He was referred to the hospital emergency department for pulmonary embolism screening. He was admitted to the internal medicine service with a diagnosis of extensive bilateral pulmonary embolism and respiratory failure. Comments: In addition to a detailed clinical history and physical examination, the active search for predisposing factors is essential in the clinical suspicion of pulmonary embolism.